Performance Improvement Of Contactless Distance Sensors - R., Abdubrani; S. S. N., Alhady (2012)
Sensor is used to detect an object and determines the distance between sensor and the object. The distance measured by the sensor is sometimes inaccurate, leading to distance errors. Two types of sensors used in this research project are Sharp GP2D12 and ultrasonic LV-Maxsonar EZ1.